Are reports of randomized controlled trials improving over time? A systematic review of 284 articles published in high-impact general and specialized medical journals. - Matthew J To; Jennifer Jones; Mohamed Emara; Alejandro R Jadad (PLoS ONE)
Background Inadequate reporting undermines findings of randomized controlled trials (RCTs). This study assessed and compared articles published in high-impact general medical and specialized journals. Methods Reports of RCTs published in high-impact general and specialized medical journals were identified through a search of MEDLINE from January to March of 1995, 2000, 2005, and 2010. Articles that provided original data on adult patients diagnosed with chronic conditions were included in the study. Data on trial characteristics, reporting of allocation concealment, quality score, and the presence of a trial flow diagram were extracted independently by two reviewers, and discrepancies were resolved by consensus or independent adjudication. Descriptive statistics were used for quantitative variables. Comparisons between general medical and specialized journals, and trends over time were performed using Chi-square tests. Results Reports of 284 trials were analyzed. There was a significantly higher proportion of RCTs published with adequate reporting of allocation concealment (p = 0.003), presentation of a trial flow diagram (p<0.0001) and high quality scores (p = 0.038) over time. Trials published in general medical journals had higher quality scores than those in specialized journals (p = 0.001), reported adequate allocation concealment more often (p = 0.013), and presented a trial flow diagram more often (p<0.001). Interpretation We found significant improvements in reporting quality of RCTs published in high-impact factor journals over the last fifteen years. These improvements are likely attributed to concerted international efforts to improve reporting quality such as CONSORT. There is still much room for improvement, especially among specialized journals.